Use of platelet-rich plasma on in vitro maturation during bovine embryo production (2024)
One of the crucial aspects to be considered for successful in vitro production (IVP) of embryos is the composition of the various media used throughout the stages of this reproductive biotechnology. The cell culture media employed should fulfill the metabolic requirements of both gametes during oocyte maturation and sperm development, as well as the embryo during its initial cell divisions. Most IVP protocols incorporate blood serum into the media composition as a source of hormones, proteins, growth factors, and nutrients. Numerous studies have suggested Platelet-Rich Plasma (PRP) as a substitute for fetal sera in cell culture, particularly for stem cells. Therefore, the objective of this study is to assess the potential use of PRP as a replacement for fetal bovine serum (FBS) during oocyte maturation for in vitro production of bovine embryos. During in vitro maturation (IVM), cumulus-oocyte complexes (COCs) were allocated into the following experimental groups: Group G1 (IVM medium with 5% PRP); Group G2 (MIV medium with 5% PRP and 5% SFB); Group G3 (MIV medium with 5% SFB); and Group G4 (MIV medium without either PRP or SFB). Subsequently, the cumulus-oocyte complexes were fertilized with semen from a single bull, and the resulting zygotes were cultured for seven days. Cleavage and blastocyst formation rates were assessed on days 2 and 7 of embryonic development, respectively. The quality of matured COCs was also evaluated by analyzing the gene expression of HSP70, an important protein associated with cellular stress. The results demonstrated that there were no significant differences among the experimental groups in terms of embryo production rates, both in the initial cleavage stages and blastocyst formation (except for the G4 group, which exhibited a lower blastocyst formation rate on D7, as expected). This indicates that PRP could be a cost-effective alternative to SFB in the IVP of embryos.